Analysis Of Consumer Behaviour Towards Mcdonald's In Bengkulu - Susena, Karona Cahya; Nabila, Melane Neysha; Tarigan , Heskyel Pranata (Utami Publisher, 2025)
This study analyses consumer behaviour towards McDonald's in Bengkulu since its arrival in 2016, considering the interaction between local cultural, social, personal and psychological factors. Using descriptive-explanatory quantitative methods, the study examined the relationship between service quality, menu adaptation (including adjustments to local flavours), promotional strategies (especially advertising that emphasises togetherness), and customer satisfaction. The results show that menu adaptation and promotional strategies that consider local cultural values have a significant effect on customer satisfaction and loyalty. These findings highlight the importance of marketing strategies that are sensitive to cultural contexts and pay attention to aspects of the overall consumer experience, not just speed and efficiency.